P.Lond. I 113.10, the exile of patriarch Kyros of Alexandria, and the Arab conquest of Egypt - Jankowiak, M (Association des Amis du Centre d’Histoire et Civilisation de Byzance, 2022)
The chronology of the patriarchate of Kyros of Alexandria, a key actor in the transition of Egypt from Roman to Arabic rule, has long been controversial. The difficulty consists in reconciling sources speaking of a long exile of around four years, in 637–41, with two documents that seem to suggest Kyros’ presence in Alexandria during this period. The first, a letter of Kyros to Patriarch Sergios of Constantinople accepting the Ekthesis, displays some unusual characteristics that suggest that Kyros was in reality in exile already by autumn 638. The second, the papyrus P.Lond. I 113.10, can be read as the sole surviving documentary trace of the tribute paid at the initiative of Kyros to stave off the Arab invasion of Egypt. The mention of Kyros as the initiator of these payments in the papyrus does not imply, therefore, his presence in Egypt in 639/40. The long exile of Kyros concords with the testimony of narrative sources, in the first place the Short history of Nikephoros, and suggests, in turn, that this text is better informed of the affairs of Egypt than has been thought since the time of Alfred Butler’s monograph on the Arab conquest of Egypt. Nikephoros’ account of several Roman campaigns to defend this province in the years preceding the invasion of ʿAmr b. al-ʿAs in 640 relocates the most detailed narrative of the Muslim conquest of Egypt, the Chronicle of John of Nikiu, in its context: that of the aftermath of the defeat of a major Roman army sent to Egypt in 639. This reconstruction of the events sheds some new light on the formation of Islamic traditions on the conquest of Egypt and the supposed Roman reoccupation of Alexandria several years later